If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -4 + -5x + 3 = x + -7 + 10 Reorder the terms: -4 + 3 + 3x + -5x = x + -7 + 10 Combine like terms: -4 + 3 = -1 -1 + 3x + -5x = x + -7 + 10 Combine like terms: 3x + -5x = -2x -1 + -2x = x + -7 + 10 Reorder the terms: -1 + -2x = -7 + 10 + x Combine like terms: -7 + 10 = 3 -1 + -2x = 3 + x Solving -1 + -2x = 3 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. -1 + -2x + -1x = 3 + x + -1x Combine like terms: -2x + -1x = -3x -1 + -3x = 3 + x + -1x Combine like terms: x + -1x = 0 -1 + -3x = 3 + 0 -1 + -3x = 3 Add '1' to each side of the equation. -1 + 1 + -3x = 3 + 1 Combine like terms: -1 + 1 = 0 0 + -3x = 3 + 1 -3x = 3 + 1 Combine like terms: 3 + 1 = 4 -3x = 4 Divide each side by '-3'. x = -1.333333333 Simplifying x = -1.333333333
| M-9=-17 | | 59/100= | | Y-14=21 | | X+80=(1.3X)+15 | | -19+46= | | X+80=(1.2X)+15 | | 2=5n-3 | | y-4=-4/7(x--2) | | -5(1-7)=-110 | | V+-9=14 | | X+80=(2(1.1X))+15 | | X+80=(1.1X)+15 | | x^3-7x^2+15x+9=0 | | 4-2(-2x+2)=4x+2 | | -1/2(7x-28) | | 6x+9=x+6 | | 9p-12=8p | | x-50.5=-16.9 | | 9(1+4n)=-279 | | 4-11b=15 | | 1/z=12/10z-8 | | g-9/9=4/9 | | 3y-5d=5d-4 | | 13+3s=-47 | | 6r+27=30 | | (x-2)(3x-12)=0 | | k-8/2=12 | | 13/8m=1/2 | | -5/2*=34 | | -2m/3=-12 | | 5(x+20)=3x+180 | | 3a-8=-6+8 |